Titanium(iv)-based helicates incorporating the ortho-phenylenediamine ligand: a structural and a computational investigation. Issue 23 (2nd June 2017) - Baradel, Nathalie; Mobian, Pierre; Khalil, Georges; Henry, Marc
Abstract : We report neutral Ti(iv )-based helical architectures formed with the ortho -phenylenediamine ligand and strands bearing 2, 2-biphenolato units. Experimental observations are explained through a computational study. Abstract : The multicomponent coordination chemistry involving Ti(OPr i )4, the ortho -phenylenediamine ligand (opda) and 2, 2′-biphenol-based proligands (L 2 H4 and L 3 H6 ) is described. The proligands L 2 H4 and L 3 H6 incorporate two and three 2, 2′-biphenol units linked with p -phenylene bridges ( p -PLB) respectively. We demonstrate that this selected set of components allows the spontaneous formation of neutral double-stranded helicates. In particular, we report the X-ray crystal structure of a multicomponent helicate formed with L2, named Ti2 (L 2 )2 (opda)2 . The molecular structure of the helicate shows two inequivalent L 2 ligands. 1 H NMR analysis at variable temperature highlights an intramolecular fluxional phenomenon for this species. An insight into this dynamic behaviour is obtained via the energy profiles of Ti2 (L 2 )2 (opda)2 resulting from the full rotation of the p -PLB rings. Additionally, the thermodynamic parameters associated with the formation of the Ti2 (L 2 )2 (opda)2 complex are modelled and discussed related to the ones linked to the formation of a related monomeric complex.